2021
DOI: 10.3389/fmats.2021.712395
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Abnormal Thermal Expansion of CuSCN and Effect on Electronic Structure

Abstract: CuSCN, as a new type of inorganic hole-transporting semiconductor with a wide bandgap (>3.4 eV), is attracting much attention in the fabrication of perovskite solar cells. In this article, by using first-principles density functional theory (DFT) and the quasi-harmonic approximation (QHA) approach, we have studied lattice dynamics and abnormal thermal expansion of the system, including α- and β-CuSCN phases. The influence of the abnormal thermal expansion of the lattice on the electronic structure, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Interestingly, it should be noted that some transverse acoustic (TA) phonon modes exhibit large negative Grüneisen parameters which also contribute greatly to the NTE of the systems. In our previous study, we found that the acoustic modes also play an important role in the NTE of the material such as Zn 2 GeO 4 , Ni 2 W­(CN) 8 , and CuSCN. , Our findings are helpful for tuning the NTE of materials.…”
Section: Introductionmentioning
confidence: 60%
“…Interestingly, it should be noted that some transverse acoustic (TA) phonon modes exhibit large negative Grüneisen parameters which also contribute greatly to the NTE of the systems. In our previous study, we found that the acoustic modes also play an important role in the NTE of the material such as Zn 2 GeO 4 , Ni 2 W­(CN) 8 , and CuSCN. , Our findings are helpful for tuning the NTE of materials.…”
Section: Introductionmentioning
confidence: 60%
“…The phonon spectra of the β-CuSCN are divided into four regions: two low-frequency regions (below 9 THZ), one intermediate-frequency region (12–12.9 THZ and 22.2–22.8 THZ), and one high-frequency region (63.9–65.4 THZ). A frequency gap of 0.32 THz around 5 THz for β-CuSCN, which reduces the number of scattering channels, elongates the phonon relaxation time, and increases lattice thermal conductivity . It can be attributed to sizable atomic mass, which decreases phonon frequency as the same as seen for MX 2 (M = Mo, W; X = S, Se, Te) .…”
Section: Resultsmentioning
confidence: 91%
“…The three acoustic phonon branches include the in-plane longitudinal acoustic (LA), transverse acoustic (TA), and out-of-plane transverse acoustic (ZA) modes, with the ZA mode having a quadratic relation at the point while the other two have linear relations. The optical phonon branches contain in-plane and longitudinal out-of-plane transverse optical modes with symmetric and antisymmetric vibrational orientations. , …”
Section: Resultsmentioning
confidence: 99%
“…The preliminary indirect band gap was 2.18 eV of β-CuSCN at 1 atm (Figure S3a), which is smaller than the experimental results. 40,41 As a result of the presence of artificial selfinteractions, this underestimation of the band gap is a wellknown problem in DFT calculations. As shown in Figure S4, the calculated band gap continuously decreases as pressure increases, and the decrease rate of the β phase band gap with increasing pressure is faster than that of the α phase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%